Calixarene-based Stationary Phases for Chromatography - Delahousse, Guillaume; Lavendomme, Roy; Jabin, Ivan; Agasse, Valerie; Cardinael, Pascal (Current Organic Chemistry, 2015)
Due to their easy functionalization and their unique conformational and recognition properties, calixarenes are attracting molecular platforms for the elaboration of separation systems. Thus, in the last decades, these macrocyclic compounds have been subject to extensive research in analytical chemistry. This review is focused on the use of calixarenes as selectors in the chromatographic separation field. The structures of calixarene derivatives and their applications as stationary phases for gas chromatography as well as high-performance liquid chromatography are described.
Keywords: selector